Application of Biotests for the Determination of Soil Ecotoxicity after Exposure to Biodegradable Plastics - Sforzini, Susanna; Oliveri, Laura; Chinaglia, Selene; Viarengo, Aldo (Frontiers in Environmental Science, 2016)
Biodegradable plastics are mostly applied in packaging materials (e.g. shopping bags), waste collection bags, catering products, and agricultural applications. In this last case, degradation takes place directly in soil where biodegradable plastic products are intentionally left after use (e.g. mulch films for weeds control). Due to the growing volumes of biodegradable polymers and plastics, interest in their environmental safety is increasing and more research is carried out. Some attempt has been made to apply biotests, used in other sectors of environmental sciences, in the assessment of biodegradable plastics safety. In this work, the quality of soils after biodegradation of the bioplastics Mater-Bi has been assessed with a large array of biotests based on model organisms representative of the different trophic levels in the food chains of the edaphic and aquatic ecosystems. Mater-Bi was degraded under controlled conditions for 6 months at a 1% concentration. The selected organisms included bacteria and protozoa (V. fischeri and D. discoideum, respectively), the green alga P. subcapitata, plants (the monocotyledon S. saccharatum and the dicotyledon L. sativum), and invertebrates animals (D. magna, a freshwater crustacean, and the Oligochaeta earthworm E. andrei), using both acute and chronic endpoints. The results of the applied ecotoxicological tests showed that the Mater-Bi materials tested at very high doses did not affect the soil quality. Soil exposed to Mater-Bi has no noxious effects on edaphic organisms; in particular, mono and dicotyledon plants results, indicate that Mater-Bi plastic products are innocuous for agricultural uses. The use of more sensitive chronic endpoints allows to exclude possible effects at population level. This is the first time that such a comprehensive approach is applied to the assessment of possible ecotoxicity effects induced by biodegradable plastics in soil and represents a possible starting point for improved standardized testing schemes.